Assessing the Implementation of Open-Knowledge Guidelines and Librarians’ Contribution to Scholarly Communications in Nigeria - Lucky Oghenetega Urhiewhu; Marian O. Nina-Okpousung; Comfort Nkeiru Udoh (Communigate, 2025)
This study assessed the implementation of open-knowledge guidelines and librarians’ contribution to academic journals in Nigeria. The study employed a descriptive research design, focusing on all librarians in Delta State. One hundred and thirteen librarians were selected through total enumeration, with data collected via a questionnaire. Analysis was conducted using descriptive statistics such as frequency, percentage, and mean. Results showed that most librarians acknowledged their lack of involvement in various academic journals. (Agg. x̄ = 2.42, Crit. x̄ = 2.50). The level of institutional support provided to librarians for engaging in academic journals is low (Agg. x̄ = 2.03, Crit. x̄ = 2.50). More so, the study revealed that the extent to which open-knowledge guidelines are implemented among the librarians is low (Agg. x̄ = 1.56, Crit. x̄ = 2.50). The study concluded that librarians struggle with broader scholarly activities because of low institutional support, inadequate training, and poor implementation of open-knowledge guidelines. These issues are further compounded by a lack of funding, technical support, mentoring, and incentives Consequently, it was suggested that the administration of institutions under study should give librarians focused opportunities for professional development to improve their research abilities, establish incentives for joint research projects involving librarians and lecturers, and set aside specific time for librarians to conduct research and publish their findings.